Development and evaluation of a cost-effective alternative media for the culture of plant pathogens - Bhattacharjee, Jayashree; Borkar, S. G.; Bhattacharjee, Debashre (Annals of Agricultural Research, 2015)
The study was conducted in search of a cost-effective alternative medium for the culture of both fungal and bacterial plant pathogens at Post Graduate Institute, M.P.K.V., Rahuri during 2012-13. Out of 3 solidifying agents evaluated at various combinations, 1 percent agar + 2 percent tapioca was found best as it formed solid transparent medium which is effective for bacterial streaking as well as fungal disc placement, therefore the quantity of agar, used in the routine medium reduced by 50 percent. Potato (200 g/L) as a source of carbohydrate and commercial sugar (2 percent) as a source of sucrose were effective in that medium for growth of both fungus and bacteria. The medium cost Rs. 52.22/L compared to Rs. 103.78/L in case of using potato dextrose agar (PDA) and Rs. 119.67/L in nutrient agar sucrose (NAS). Therefore, it was suggested that, tapioca-potato-sugar-agar (TPSA) could be a cost-effective alternative medium for working with both fungus and bacteria of pant origin.